Pengaruh Kualitas Pelayanan, Harga, dan Lokasi Terhadap Kepuasan Konsumen Pada Bank Syariah KCP Probolinggo - Nurweni, Nurweni; Ngatimun, Ngatimun; Pujiastuti, Agustina (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
Objective the purpose of this study is to determine the partial effect of service quality, price, and location on customer satisfaction at Bank Syariah.service quality, price,and location on customer satisfaction at Bank SyariahIndonesia KCP ProbolinggoCity. The type of research used isquantitative with an associative approach.The population in this study isconsumers of Bank Syariah Indonesia ProbolinggoCity in the February-March 2024 period. The number of samples inThis studywas 52 obtained from the calculation of the slovin formula. Inprove and analyze this, the validity and reliability tests, classical assumption tests, classicreliability, classical assumption test, multiple linear analysis, analysis of the coefficient of determination R2,Hepot test.determination coefficient analysis R2, Hepotesi test. The results showed that the quality ofservice (X1) price (X2) location (X3)partially and significantly affect customer satisfaction (Y).